Pattern recognition receptors in zebrafish provide functional and evolutionary insight into innate immune signaling pathways - Li, Yajuan; Li, Yuelong; Cao, Xiaocong; Jin, Xiangyu; Jin, Tengchuan (Cellular & molecular immunology, 2017)
Pattern recognition receptors （PRRs） and their signaling pathways have essential roles in recognizing various components of pathogens as well as damaged cells and triggering inflammatory responses that eliminate invading microorganisms and damaged cells. The zebrafish relies heavily on these primary defense mechanisms against pathogens. Here, we review the major PRR signaling pathways in the zebrafish innate immune system and compare these signaling pathways in zebrafish and humans to reveal their evolutionary relationship and better understand their innate immune defense mechanisms.